Regulation - Clarke, M. author. aut Link
VI, 249 p.
Keywords: Regulation has been stimulated by industrialisation and particularly by the advent of the consumer economy. This book draws on international scholarship in sociology, political science, law and economics on the working and regulation, both in public and private, in many areas of business to map the reality of regulation, and to identify why it sometimes fails and how it can succeed.